A Study on the Determination of Fish Species Diversity in Pamucak Artificial Reefs in Kuşadası Bay Aegean Sea - ULAŞ, Ali; SERDAR, Serpil; YILDIRIM, Şükrü; GÖKTÜRK, Didem (MAS Journal of Applied Sciences, 2023)
This study which was carried out between September 2019 and May 2020 in the 822m³ artificial reef area created in 2001 on the Pamucak coast of Kuşadası Bay aimed to determine the species diversity and individual density in the Pamucak artificial reef area and to determine the prevention efficiency of illegal fishing gear of artificial reefs in the region. The sampling of artificial reefs was determined by visual counting method by performing SCUBA diving. At the end of the 12-month study, 4522 individuals belonging to 30 fish species in 12 families were identified. Oblada melanura was determined as the most numerous (2475 species) observed on artificial reefs in every month of the year. Choromis chromis was observed in the second place with 843 individuals, while the Diplodus vulgaris was observed in the third place with 319 individuals every month. Paracentrodus lividus and Aplysia elongata are the first invertebrate species observed every month in the artificial reef area. In the artificial reef area, the highest water temperature was recorded as 26 °C in August and the lowest temperature was recorded as 14.9 °C in March. The lowest dissolved oxygen value was measured in April with 8.18 mg/L and the lowest dissolved oxygen value in October with 7.10mg/L. The minimum salinity was 37.19 mg/L per thousand in January, and the highest salinity was 39.91 mg/L in June. The highest visibility was 17 m in August and the lowest was 2.5 m in October. During underwater observations, it was determined that approximately 74 m² of reef area in artificial reefs was covered with fishing nets illegally used. 82 % of the nets were determined as purse seiners and 18 % as gillnets. As a result, the density of species and individuals, mainly fish, was determined in the artificial reef area, and it was concluded that artificial reefs constitute an obstacle to illegal fishing in the region with the detected ghost nets.